Prevalence of caries and gingivitis among school children in the municipality of Foča - Đorđević Stevanka; Ivanović Tanja; Žuža Aleksandra; Nogo-Živanović Dajana; Kulić Ljiljana (Serbian Medical Society - Dental Section, Belgrade, 2012)
Introduction. The aim of this study was to determine the prevalence of caries and gingivitis among adolescents who attend school in the municipality of Foca, Republika Srpska. Material and Methods. The total number of 352 school children - 135 students of the ninth grade of primary school (aged 15 years) and 217 students of the third and fourth grade of high school (aged 17-18 years) - were included in this cross-section study. The incidence of dental caries using DMFT index and its components was calculated as recommended by the World Health Organization. Periodontal tissue condition was determined using gingival index (GI) by Löe and Silness. Results. The mean DMFT in students age 15 was 6.6, and in students age 17-18 was 9.5. The dominant components of DMFT index in both studied groups were filled and carious teeth. In regards to gender, female students age 15 had significantly greater number of extracted teeth than male students (p<0.05). In older age group, females had significantly more filled teeth than males (p<0.05). Mild gingivitis was present in both studied groups. Conclusion. Our results showed that caries prevalence in the tested groups was high and mild gingivitis was present in most patients.